DETERMINING MORE PRECISE OPTIMUM NITROGEN RATE FOR EFFECTIVE TESTING OF RHIZOBIA ON GROUNDNUT (Arachis hypogaea L.) IN THE GLASSHOUSE - ABDULLAHI, A. A.; ABUBAKAR, F. J.; OYEDELE, A. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
A study was conducted to determine the adequate mineral N requirement of groundnut (Arachis hypogaea L.) for comparison with rhizobia strains in the glasshouse. Ten treatments, six mineral N rates (0, 0.2, 0.5, 1.0, 3.0 and 5.0 mmoles of N twice a week), three indigenous rhizobia (KBU 026, SNN 335 and SNN 345) and a standard rhizobia strain (NC 92) were involved. These were laid down in a Randomized Complete Block Design (RCBD), replicated five times with SAMNUT 24 as a test crop. The plants were harvested at six weeks after sowing. Shoot dry matter, flowers and N uptake of the plants, were determined, and subjected to analysis of variance (ANOVA). The results showed significant differences (P < 0.01) among the treatments in influencing all the parameters. The 0.5, 1.0, 5.0, 3.0, 0.2 and SNN 335 gave 88, 86, 85, 39, 23 and 15% higher shoot dry matter relative to 0 mmoles N control, respectively. While increases of 71, 67, 50, 50, 71, 33 and 50% flowers were observed on application of 0.5, 3.0, 5.0 ,1.0, KBU 026, NC 92 and SNN 335, respectively, relative to 0 mmoles N. Therefore, the application of 0.5 mmoles twice week-1 gave higher influence on shoot dry matter, flowers and N uptake relative to other N rates. KBU 026 and SNN 335 performed similar to the application of other N rates as shown by the percentages. The study indicates 0.5 mmoles twice a week-1 (1.0 mmoles N week-1) as the precise optimum N application rate that could facilitate N economy and accurate effectiveness testing of rhizobia strains on groundnut in the glasshouse.